2018
DOI: 10.1002/2017wr021388
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Dissolved Oxygen Concentrations and Bioactivity in the Hyporheic Zone

Abstract: Dissolved oxygen (DO) concentrations and consumption rates are primary indicators of heterotrophic respiration and redox conditions in the hyporheic zone (HZ). Due to the complexity of hyporheic flow and interactions between hyporheic hydraulics and the biogeochemical processes, a detailed, mechanistic, and predictive understanding of the biogeochemical activity in the HZ has not yet been developed. Previous studies of microbial activity in the HZ have treated the metabolic DO consumption rate constant (KDO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 70 publications
3
48
0
1
Order By: Relevance
“…The overall CFD modeling approach was validated against the pressure measurements provided by Fehlman (). Excellent agreement between the simulated and measured bed‐pressures, over a broad range of discharges and energy head, gave us a high degree of confidence that our modeling approach was robust, accurate, and not overly sensitive to the applied boundary conditions (Reeder, Quick, Farrell, Benner, Feris, & Tonina, ).…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…The overall CFD modeling approach was validated against the pressure measurements provided by Fehlman (). Excellent agreement between the simulated and measured bed‐pressures, over a broad range of discharges and energy head, gave us a high degree of confidence that our modeling approach was robust, accurate, and not overly sensitive to the applied boundary conditions (Reeder, Quick, Farrell, Benner, Feris, & Tonina, ).…”
Section: Methodsmentioning
confidence: 72%
“…In Reeder, Quick, Farrell, Benner, Feris, and Tonina (), we showed that, for dune‐like bedforms, K DO values are lognormally distributed and that flowline K DO values can be calculated from the mean K DO , Ktrue¯DO, and the standard deviation, σ KDO . They can be estimated by using the log transform variable, Y = ln( K DO ), the log transform mean, μ Y , and the standard deviation, σ Y , from the inverse normal distribution: KDO=exp()F1|()X*μY,σY, where F|()YμY,σY=1σY2πoYelnξμY220.25emσY2normaldξ, where ξ is a dummy variable of integration and X* is the dimensionless, horizontal distance along the upstream downwelling face of the bedform, defined as X*=x/λ, with λ ′ as the horizontal length of the downwelling face of the bedform.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…This inference is supported by Peclét and Damköhler calculations >1 for each location and time point, suggesting that the DO transport‐induced oxygen consumption reaction controls porewater concentrations of DO (Saup et al, ; equations S1 and S2). Previous work on the lateral distribution of microbial respiration rates also found that DO and nutrient concentrations influence spatial and temporal “hot spots” of biogeochemical activity within the hyporheic zone (King et al, ; Reeder et al, ). In contrast to the vertical exchange measured here at the East River site, the introduction and rapid depletion of DO along lateral hyporheic flow paths through the floodplain have also been modeled at East River, indicating that complete oxygen consumption occurs over ~1‐m distances into the floodplain (Dwivedi et al, ).…”
Section: Resultsmentioning
confidence: 93%